Metatarsophalangeal Joint Arthrodesis for Severe Hallux Valgus in Elderly Patients. Issue 8 (August 2017) - Perugia, Dario; Calderaro, Cosma; Iorio, Carlo; Civintenga, Carolina; Lepri, Marco; Masi, Vincenzo; Ferretti, Andrea
Abstract : Severe hallux valgus is a common condition involving pain and limitation of range of motion (ROM) of the first metatarsophalangeal (MTP) joint; the condition is frequently associated with degenerative arthritis. Conservative treatments, such as activity modification, stiff-soled shoes, orthoses, NSAIDs, and cortisone injections, have only short-term effectiveness. Commonly performed surgical techniques include proximal osteotomy or distal osteotomy with extreme bone translation that can be associated with other joint-sparing procedures such as cheilectomy, phalangeal osteotomy, and shortening first metatarsal osteotomy. Despite this, pain, ROM limitation, and functional impairment often remain. Although few published studies exist, arthrodesis of the first MTP joint is a reliable procedure to address this condition, with good to excellent results. Postoperatively, weight bearing on the heel in a postoperative shoe is allowed; walking flatfooted is permitted after radiographic healing has been achieved (typically, 4 to 6 weeks). Potential complications include the general surgery risks associated with anesthesia, infection, damage to nerves, and bleeding. Complications specific to MTP fusion include delayed bone healing, malunion, nonunion, and stiffness in neighboring joints. MTP arthrodesis is a reliable and successful procedure to correct severe hallux valgus, especially in elderly patients, with a high rate of bone fusion, with a low rate of complications, without impairment of the ambulation, and without need of a special postoperative rehabilitation protocol. Watch the video trailer:http://links.lww.com/JAAOS/A40 .